Opinion of the European Copyright Society on Certain Selected Aspects of Case C-227/23, Kwantum Nederland and Kwantum België - Mireille van Eechoud; Axel Metzger; Jo\~ao Pedro Quintais; Ole-Andreas Rognstad (IIC - International Review of Intellectual Property and Competition Law, 2024)
Abstract The Berne Convention underscores the national treatment of foreign authors, allowing countries of the Union to protect designs through various means. Article 2(7) of the Convention (Berne) introduces a material reciprocity test, limiting copyright protection for works of applied art not protected in their country of origin. The Kwantum case (C-227/23), involving a dispute over a work of design or applied art, questions the application of the reciprocity test in the light of harmonised copyright law and the decision by the Court of Justice of the European Union (CJEU) in RAAP (C-265/19). The Dutch Supreme Court seeks clarity on whether EU law mandates a~copyright limitation through reciprocity, especially for non-EU right holders. In EU law, the Design Directive and Design Regulation govern the relationship between copyright and design protection for works of applied art. Both instruments stress the possibility of the cumulation of rights, allowing registered designs to qualify for copyright protection. Judicial harmonisation, notably in Cofemel (C-683/17) and Brompton Bicycle (C-833/18), extended the originality requirements to all works – including works of applied art – and thus limited EU Member States' autonomy. The proposed Design Directive and Design Regulation maintain the cumulation principle, aligning with CJEU case-law on originality. In this Opinion, the European Copyright Society (ECS) does not make any pronouncement on the desirability of cumulation. On the topic of material reciprocity, the CJEU ruled in RAAP that Art. 8(2) of the Rental and Lending Directive (RLD) prohibited a Member State from excluding non-EEA performers from equitable remuneration for communication to the public of their recordings. The Court clarified that limitations to this right could be introduced only by the EU legislature and had to comply with Art. 52(1) of the Charter of Fundamental Rights of the European Union (CFREU). Any limitation had to be clearly defined by law. The Court emphasised that any exclusion of non-EEA right holders from remuneration must be explicit, as the right fell within the fundamental right to intellectual property of Art. 17(2) CFREU. Additionally, the Court stated that Art. 8(2) RLD should not be interpreted as granting a remuneration right solely to the phonogram producer and excluding the performer who contributed to the phonogram. The ECS criticised the potential wider implications of RAAP , proposing an alternative interpretation of the remuneration right under Art. 4(2) of the WIPO Performance and Phonograms Treaty (WPPT), suggesting that it should apply only to performers towards whom a direct and unreserved obligation existed on the basis of the WPPT. The ECS also criticised the Court's reliance on the CFREU, particularly insofar as the Court viewed harmonised rights as abstract rather than individual, thus creating uncertainty about limitations. The Court's conclusion that only the EU legislature could limit the right for nationals of non-EU states raises concerns about the application of material reciprocity by Member States in the past, and the retroactive effects of the interpretation remain unclear, contributing to legal uncertainty. In RAAP , the CJEU interpreted the WPPT, emphasising compliance with TRIPS and the Berne Convention's core provisions in EU law. The Court stressed that material reciprocity had to be explicit in statutory law, with only the EU legislature defining limitations under harmonised rules such as Art. 8(2) RLD. However, EU design legislation grants Member States autonomy despite harmonised concepts established in cases like Cofemel and Brompton Bicycle . Unlike in RAAP , the CJEU may have more flexibility in interpreting EU copyright law for applied art in the Kwantum case. Precedents like Cofemel and Brompton Bicycle allow the Court to interpret material reciprocity under Art. 2(7) Berne without legislative intervention. Two alternatives for the Court are to interpret Art. 2(7) as mandating material reciprocity, preventing internal market issues, or to declare Member States' application compatible with EU law, whether they apply material reciprocity or offer unreserved national treatment to works of applied art on the basis of Art. 19 Berne. Comparing RAAP and Kwantum , material reciprocity differs under Art. 4(2) WPPT and Art. 2(7) Berne. RAAP dealt with a conditional exception, while Art. 2(7) Berne is a mandatory rule, implying that countries of the Union must deny copyright protection to works protected solely as designs and models in their country of origin. While countries can choose to set aside material reciprocity under Art. 19 Berne, if the CJEU views Art. 2(7) Berne as limiting copyright as an intellectual property right under Art. 17(2) CFREU, the requirements in Art. 52(1) CFREU are already fulfilled without legislative intervention. Applying these considerations to the Kwantum case, it is noted that Dutch law provides no more protection than Art. 2(7) Berne. Given Art. 2(7)'s precedence over domestic law in the Dutch legal order, Dutch courts must apply the material reciprocity clause unless EU law dictates otherwise. In our view, the CJEU could either recognise material reciprocity as a requirement of EU law or declare Member State rules that mirror Berne's reciprocity clause to be compatible with EU law. In conclusion, Kwantum reflects the uncertainty stemming from RAAP . The ECS advocates for a nuanced approach to the international application of EU copyright and related rights, giving due consideration to the regulations of international conventions as part of the EU legal order. In the case of copyright protection of works of applied art, the CJEU could, as a first step, either apply the reciprocity rule set out in Art. 2(7) Berne directly, or leave it to the Member States to decide on material reciprocity or national treatment, in accordance with the principles of the Berne Convention. As a second step, the EU legislature would be well advised to address the questions raised by RAAP and Kwantum at a more fundamental level through legislative intervention.
Keywords: 330; Kwantum Nederland and Kwantum België; Copyright law; RAAP; Applied art